219k views
4 votes
to solve a system using the additional method, you would need to multiply the first equation by what number in order for the x’s to add out? 3x-y=3, -2x+2y=6

1 Answer

3 votes

Answer:

2

Explanation:

In order to solve a system using the additional method, we would need to multiply the first equation by '2' in order for the x’s to add out.

We have the following equations:


3 x - y = 3 --- (1)


-2x + 2y = 6 --- (2)

We will multiply equation (1) by 2 and equation (2) by 3 to cancel the x's.


2 ( 3x - y = 3 ) =
6x - 2 y = 6


3 ( -2x + 2 y = 6 ) = -6x + 6y = 36

User Aphid
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.